2018
DOI: 10.1016/j.trsl.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of semicarbazide-sensitive amine oxidase reduces atherosclerosis in apolipoprotein E-deficient mice

Abstract: Inflammation, oxidative stress, and formation of advanced glycated end products (AGEs) and advanced lipoxidation end products (ALEs) are important for atherosclerosis. Vascular adhesion protein-1 (VAP-1) participates in inflammation and has semicarbazide-sensitive amine oxidase (SSAO) activity, which catalyzes oxidative deamination to produce hydrogen peroxide and aldehydes, leading to generation of AGEs and ALEs. However, the effect of VAP-1/SSAO inhibition on atherosclerosis remains controversial, and no stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“…By contrast, in LDLr −/− ApoB 100/100 mice on WTD, Sivola et al demonstrated that 4-weeks treatment with JLP-1586, another VAP-1 inhibitor, had no effect on plaque size, body weight, or plasma lipid levels, but decreased the density of macrophages in atherosclerotic lesions ( Silvola et al, 2016 ). In addition, Wang et al found that ApoE −/− mice or rabbits treated with PXS-4728A, a specific SSAO inhibitor, exhibited reduced atheroma with less oxidative stress and endothelial dysfunction, and markedly alleviated plasma levels of lipids and glucose ( Wang et al, 2018a ; Wang et al, 2018b ). Given that comparable LDL-C/glucose lowering by atorvastatin resulted in a similar reduction of lesions, it seems that the atheroprotective effect of PXS-4728A is largely attributed to the reduced levels of LDL-C/glucose.…”
Section: Vap-1: An Important Player In Atherosclerosismentioning
confidence: 99%
“…By contrast, in LDLr −/− ApoB 100/100 mice on WTD, Sivola et al demonstrated that 4-weeks treatment with JLP-1586, another VAP-1 inhibitor, had no effect on plaque size, body weight, or plasma lipid levels, but decreased the density of macrophages in atherosclerotic lesions ( Silvola et al, 2016 ). In addition, Wang et al found that ApoE −/− mice or rabbits treated with PXS-4728A, a specific SSAO inhibitor, exhibited reduced atheroma with less oxidative stress and endothelial dysfunction, and markedly alleviated plasma levels of lipids and glucose ( Wang et al, 2018a ; Wang et al, 2018b ). Given that comparable LDL-C/glucose lowering by atorvastatin resulted in a similar reduction of lesions, it seems that the atheroprotective effect of PXS-4728A is largely attributed to the reduced levels of LDL-C/glucose.…”
Section: Vap-1: An Important Player In Atherosclerosismentioning
confidence: 99%
“…Increased metabolic enzyme expression is associated with the development of diabetes and diabetic complications. Enzymes in the SSAO family form MG during amino acid breakdown and are highly expressed in adipose tissue and in endothelial cells. , Inhibiting SSAO enzymes decreased MG levels, protected pancreatic beta-cells, decreased weight gain and fat deposition, and alleviated the symptoms of diabetic complications. AR forms MG through the polyol pathway and is associated with the development of many diabetic complications; it was first described for its role in causing lens damage . Its inhibition decreased MG levels and the incidence of diabetic complications. , Intriguingly, MG increased the expression and activity of AR .…”
Section: Expression Of Mg-regulating Enzymes In Disease and Strategie...mentioning
confidence: 99%
“…First, the mild obesity of these mice strikingly contrasts with the decreased fattening found in rodents treated by pharmacological inhibitors of SSAO, such as hydralazine [49] , a fluoroallylamine derivative [50] , semicarbazide [51] or phenelzine [52,53] . A better understanding of the selectivity of these inhibitors will help to explain these apparent inconsistencies, as all of them have "off-target" actions (for reviews, see [9,54] ). Second, the pharmacological inhibition of VAP-1/SSAO has been reported to be beneficial for experimental atherosclerosis in mice and rabbits [55,56] .…”
Section: Oxidative Stress and Aorta No Bioavailability In Aoc3ko Micementioning
confidence: 99%